France’s Intervention Policy in Africa Seen from Below: Some Thoughts on the Case of Côte d’Ivoire - (:unkn) unknown (My University, 2014)
In contradiction with the promise to break with its post-colonial past and someattempts to change its foreign policy, France has reengaged itself massively in African crises.The military interventions launched in Côte d’Ivoire, Mali and Central African Republicseem to define a new French interventionist policy South of the Sahara. Based upon extensivesurveys conducted in Côte d’Ivoire among young pro-Gbagbo militants, this article tries tointerpret this new stance from below. It contends that the nationalist and anti-colonial mobilisationsthat took place in the country were not only instrumental in local power bargaining.They were (and are still) a powerful leverage for generational emancipation and reflect someconflicts of subjectification which will be key in the evolution of Franco-African relations inthe future.
Keywords: African Research